Handbook of Gendered Careers in Management 2015
DOI: 10.4337/9781782547709.00014
|View full text |Cite
|
Sign up to set email alerts
|

Presumed incompetent: perceived lack of fit and gender bias in recruitment and selection

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 37 publications
0
55
0
1
Order By: Relevance
“…Communication and co-operation are generally assumed to be abilities with a feminine touch (Billing and Alvesson, 2000;Prime et al, 2009). It has been suggested that these abilities are more related to femininity and women, than to men (Prime et al, 2009;Heilman et al, 2015). Following this logic women are claimed to be emotional, sensitive and good at communication.…”
Section: Gendering the Expert Candidacy In The Job Advertisementsmentioning
confidence: 99%
“…Communication and co-operation are generally assumed to be abilities with a feminine touch (Billing and Alvesson, 2000;Prime et al, 2009). It has been suggested that these abilities are more related to femininity and women, than to men (Prime et al, 2009;Heilman et al, 2015). Following this logic women are claimed to be emotional, sensitive and good at communication.…”
Section: Gendering the Expert Candidacy In The Job Advertisementsmentioning
confidence: 99%
“…Organizations are also gendered spaces which establish and reproduce gendered regimes which impact on recruiting and promotion policies for management positions (Hannappi-Egger, 2015). Heilman et al (2015) use the 'lack of fit' model to demonstrate how gender-based expectations result in different interpretations of the same behaviour and how stereotypes are reinforced. In many organizations, therefore, women continue to be treated less favourably than men (Eagly and Carli, 2007;Powell, 2012), are regarded as less competent (Heilman, 2001;Prime et al, 2008), are highly scrutinized in a way that does not apply to men (Eagly and Carli, 2007;Ryan and Haslam, 2005) and have to work harder than men (Mavin et al, 2015).…”
Section: Part Iv: Gendermentioning
confidence: 99%
“…This lack of stereotype fit or incongruence results in women being “presumed incompetent” in professional roles (Heilman, Block, & Lucas, 1992; Heilman, Manzi, & Braun, 2015), and in shifting standards in performance evaluation (Biernat & Fuegen, 2001). Women who display stereotypically male behavior such as assertiveness and self-promotion in a work environment may experience penalties and backlash (Rudman & Phelan, 2008).…”
Section: Mitigating Bias In Selection and Promotion Decisionsmentioning
confidence: 99%